Development of the Method for Determination of Volatile Sulfur Compounds (VSCs) in Fruit Brandy with the Use of HS–SPME/GC–MS - Urszula Dziekońska-Kubczak (Molecules, 2020)
Volatile sulfur compounds (VSCs) play an important role in the aroma profile of fermented beverages. However, because of their low concentration in samples, their analysis is difficult. The headspace solid-phase microextraction (HS−SPME) technique coupled with gas chromatography and mass spectrometry (GC−MS) is one of the methods successfully used to identify VSCs in wine and beer samples. However, this method encounters more obstacles when spirit beverages are analyzed, as the ethanol content of the matrix decreases the method sensitivity. In this work, different conditions applied during HS−SPME/GC−MS analysis, namely: ethanol concentration, salt addition, time and temperature of extraction, as well as fiber coating, were evaluated in regard to 19 sulfur compounds. The best results were obtained when 50/30 μm Divinylbenzene/Carboxen/Polydimethylsiloxane (DVB/CAR/PDMS) was used to preconcentrate the analytes from the sample at 35 °C for 30 min. The dilution of samples to 2.5% v/v ethanol and the addition of 20% w/v NaCl along with 1% EDTA significantly improves the sensitivity of extraction. The optimized method was applied to three fruit brandy samples (plum, pear, and apple) and quantification of VSCs was performed. A total of 10 compounds were identified in brandy samples and their concentration varied greatly depending on the raw material used from production. The highest concentration of identified VSCs was found in apple brandy (82 µg/L).